Kajian Yuridis Tindak Pidana Gratifikasi Oleh Pejabat Negara - Bustomi Bustomi (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2024)
Corruption is a special criminal act that is regulated outside the Criminal Code (KUHP). Especially because this issue is regulated separately outside the Criminal Code (Criminal Code). Because in accordance with Article 103 of the Criminal Code, it is emphasized that: